Characterization of Chitosan Obtained from Snail Shell (Achatina fulica) and its Excipient Potentials in Metronidazole Tablet Formulation - Bamiro, Oluyemisi Adebowale; Salisu, Aishat Oyinkansola; Iyere, Ese Mary; Atoyegbe, Olatundun; Adeleye, Olutayo Ademola; Bakre, Lateef Gbenga (Dhaka University Journal of Pharmaceutical Sciences, 2021)
The aim of the work was to characterize chitosan extracted from snail shell and evaluate its use as a disintegrant and binder in metronidazole tablet formulation in comparison with standard chitosan (SC). The mechanical properties were assessed using crushing strength and friability, while the release properties were assessed using disintegration and dissolution times. The extracted chitosan (EC) was crystalline in nature and the scanning electron microscopy (SEM) showed polygonal particles with rough surface. The moisture and swelling capacity was 1.80% and 15.00%, respectively. The densities and flow properties were significantly (p<0.05) higher than those of the SC. As a binder, the crushing strength of formulations containing EC was higher than SC, but both formulation failed friability test. There was significant difference between the disintegration times of the metronidazole formulations containing EC and SC as a disintegrant. The result showed that EC is more effective as a binder in tablet formulations. Dhaka Univ. J. Pharm. Sci. 20(1): 31-39, 2021 (June)